The effect of musical expertise on the representation of space - Lega, Carlotta; Cattaneo, Zaira; Merabet, Lotfi B.; Vecchi, Tomaso; Cucchi, Silvia (Frontiers in Human Neuroscience, 2014)
Consistent evidence suggests that pitch height may be represented in a spatial format, having both a vertical and an horizontal representation. The spatial representation of pitch height results into response compatibility effects for which high pitch tones are preferentially associated to up-right responses, and low pitch tones are preferentially associated to down-left responses (i.e., the SMARC effect), with the strength of these associations depending on individuals’ musical skills. In this study we investigated whether listening to tones of different pitch affects the representation of external space, as assessed in a visual and haptic line bisection paradigm, in musicians and non musicians. Low and high pitch tones affected the bisection performance in musicians differently, both when pitch was relevant and irrelevant for the task, and in both the visual and the haptic modality. No effect of pitch height was observed on the bisection performance of non musicians. Moreover, our data also show that musicians present a (supramodal) rightward bisection bias in both the visual and the haptic modality, extending previous findings limited to the visual modality, and consistent with the idea that intense practice with musical notation and bimanual instrument training affects hemispheric lateralization.